Relationship between Stock Return, Trading Volume, and Trading Price of Agriculture Development Bank (Pravaha, 2021)
The main objective of the study is to measure the causal relationship between stock return, trading volume, and the trading price of Agriculture Development bank. Descriptive research and casual comparative research designs have been used to analyze the study. The 11years panel data has been used. The 2104 observations are analyzed to draw a valid conclusion about the study. The descriptive model provides evidence of average stock return, trading volume, and price volatility. The investors of ADB faced high risk in stock investment during the 11 years. There is a significant positive relationship between them. Similarly, there is a positive and significant impact of trading volume and trading price on stock return.